PWE-158 Thymosin Beta 4 as a Putative Marker in Neuroendocrine Tumours. (4th June 2013) - Mandair, D; Marotta, D; Ho, J; Waugh, M; Srirajaskanthan, R; Woffendin, G; Caplin, M; Hsuan, J; Beaumont, N
Abstract : Introduction: Neuroendocrine tumours (NETS) arise from the diffuse endocrine system which produce biogenic amines and peptides that could be potential biomarkers. We previously analysed proteomes secreted by NET cell lines and identified mac2BP as putative marker which was also elevated in patients compared to healthy controls Methods: 3 Cell Lines BON-1, NCI-H727, and SHP-77 cells were grown in serum-free media overnight, which was then fractionated and the secreted 3–10kDa polypeptides were identified using Tandem Mass spectrometry. One of the small proteins, Thymosin β4 was measured in serum samples of patients and controls using ELISA. Mac2BP & chromogranin A was also measured Results: 70 proteins were secreted by all three lines, including 20 small proteins of which 3 were thymosins α1, β4 & β10. Serum samples were analysed in 34 patients and 24 healthy controls. Thymosin β4 was elevated in the serum of NET patients compared with healthy controls (p < 0.002). The area under the curve was 0.84 following ROC analysis. Conclusion: Mass spectrometry of the secretomes of 3 NET cell lines offers a novel way of identifying potential biomarkers. Thymosin β4 could be such a biomarker but further examination of tissue and other cell lines is necessary. A further analysis of serum from larger groups of patients both pre and post therapy is needed. Disclosure of Interest: None Declared.